Clinical characteristics of new-onset acute kidney injury in patients with established acute respiratory distress syndrome: A prospective single-center post hoc observational study - Cui, Xiaoyang; Huang, Xu; Yu, Xin; Cai, Ying; Tian, Ye; Zhan, Qingyuan (Frontiers in Medicine, 2022)
Background: We assessed the incidence and clinical characteristics of acute kidney injury (AKI) in acute respiratory distress syndrome (ARDS) patients and its effect on clinical outcomes. Methods: We conducted a single-centre prospective longitudinal study. Patients who met the Berlin definition of ARDS in the medical ICU in China-Japan Friendship Hospital from March 1, 2016, to September 30, 2020, were included. AKI was defined according to the KDIGO clinical practice guidelines. Early and late AKI were defined as AKI occurring within 48 h after ARDS was diagnosed or after 48 h, respectively. Results: Of the 311 ARDS patients, 161 (51.8%) developed AKI after ICU admission. Independent risk factors for AKI in ARDS patients were age (OR 1.027, 95% CI 1.009–1.045), a history of diabetes mellitus (OR 2.110, 95%CI 1.100–4.046) and chronic kidney disease (OR 9.328, 95%CI 2.393–36.363), APACHE II score (OR 1.049, 95%CI 1.008–1.092), average lactate level in the first three days (OR 1.965, 95%CI 1.287–3.020) and using ECMO support (OR 2.359, 95%CI 1.154–4.824). Early AKI was found in 91 (56.5%) patients and late AKI was found in 70 (43.5%). Early AKI was related to the patient's underlying disease and the severity of hospital admission, while late AKI was related to the application of nephrotoxic drugs. The mortality rate of ARDS combined with AKI was 57.1%, which was independently associated with shock (OR 54.943, 95%CI 9.751 to 309.573). Conclusions: A significant number of patients with ARDS developed AKI, and the mortality rate for ARDS patients was significantly higher when combined with AKI. Therapeutic drug monitoring should be routinely used to avoid drug toxicity during treatment.